2017
DOI: 10.5603/demj.2017.0001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Miller and Macintosh laryngoscopes in simulated pediatric trauma patient: a pilot study

Abstract: INTRODUCTION: Airway management in pediatric trauma patients is challenging. Direct laryngoscopy is the gold standard for endotracheal intubation in emergency and trauma patients. The aim of the present study was to evaluate the performance of Miller (MIL) and Macintosh (MAC) laryngoscopes when employed in emergency pediatric intubation scenarios. METHODS: This was a prospective, randomized, crossover, single-center study on novice physicians recruited on a voluntary basis. Each participant performer endotrach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Numerous studies indicate that in pediatric patients over 2 years of age, laryngoscopes with both Miller and Macintosh blade can be used with comparable effectiveness [36]. In turn, Eisenberg et al [10] showed that in a pediatric emergency department, the first intubation effectiveness with the use of direct laryngoscopy was only 71%.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicate that in pediatric patients over 2 years of age, laryngoscopes with both Miller and Macintosh blade can be used with comparable effectiveness [36]. In turn, Eisenberg et al [10] showed that in a pediatric emergency department, the first intubation effectiveness with the use of direct laryngoscopy was only 71%.…”
Section: Discussionmentioning
confidence: 99%
“…Intubation of the tracheal tube allows complete isolation of the airways, thus preventing aspiration of the alimentary tract to the respiratory tract and subsequent toxic pneumonitis [14]. It should be remembered that in out-of-hospital settings, each patient should be treated as a patient with potentially difficult airways; the patient can have a full stomach, as well as the potential to encounter anatomical anomalies in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…Bielski et al [19] indicate that blind intubation is also possible in the case of traumatic patients and using other vigilant devices. In the study by Bielski et al [19], paramedics performed intubation of a patient stuck in a vehicle with a Macintosh laryngoscope and blind intubation using an iGEL laryngeal mask, achieving a significant reduction in the duration of the procedure in the case of blind intubation than direct laryngoscopy (15 [IQR,(12)(13)(14)(15)(16)(17)(18)(19) vs. 43 [IQR, 38-59], p < 0.001). In turn, Ladny et al [20] indicated that chest compressions do not affect the time necessary for blind intubation via various SADs performed by nurses.…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods of carrying a victim on a stretcher, which depends on the number of rescuers or people who will perform this task [13]. The most atraumatic method can be used when five people are available.…”
Section: Instrumented Means Of Evacuation Of An Injuredmentioning
confidence: 99%